2019
DOI: 10.1111/jocn.15002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of health education by telephone follow‐up on self‐efficacy among discharged patients with rheumatoid arthritis: A randomised control trial

Abstract: Aims and objectives To explore the effectiveness of a health education programme by telephone follow‐up on the self‐efficacy of patients with rheumatoid arthritis (RA). Background Self‐efficacy is increasingly perceived to be a cornerstone in improving the capacity of self‐management. However, a paucity of research has demonstrated the effectiveness of health education by the use of a telephone follow‐up for RA patients in China. Design This study was a randomised control trial. Methods Recruited patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 14 publications
(19 reference statements)
1
37
0
Order By: Relevance
“…Several RCT studies on patient education for people with IA have shown positive effects on different outcomes such as self‐efficacy (Grønning et. al , Zhao & Chen, ), pain, fatigue, illness perception, quality of life, sedentary time (Knittle et al,) and overall well‐being (Grønning et. al , Grønning et.…”
Section: Introductionmentioning
confidence: 99%
“…Several RCT studies on patient education for people with IA have shown positive effects on different outcomes such as self‐efficacy (Grønning et. al , Zhao & Chen, ), pain, fatigue, illness perception, quality of life, sedentary time (Knittle et al,) and overall well‐being (Grønning et. al , Grønning et.…”
Section: Introductionmentioning
confidence: 99%
“…(17). The same study was conducted on patients with Rheumatoid Arthritis by monitoring their emotions four times (18).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, planned educational interventions will be given by telephone four times for 12 weeks. Specialist rheumatology nurses carried out this telephone educational intervention at weeks 2, 4, 8, and 12 weeks after the patient was discharged from the hospital (18).…”
Section: Combining Face-to-face Education With Indirect Educationmentioning
confidence: 99%
“…One study was assessed to have high risk of attrition bias as the data was incomplete [24]. All studies were unclear or at high risk of bias in most domains, common issues included small numbers of participants and a lack of blinding [20][21][22][23].…”
Section: Quality Assessment and Risk Of Biasmentioning
confidence: 99%